2018
DOI: 10.1371/journal.pone.0209016
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate multiple regression models of poly(ethylene-terephthalate) film degradation under outdoor and multi-stressor accelerated weathering exposures

Abstract: Developing materials for use in photovoltaic (PV) systems requires knowledge of their performance over the warranted lifetime of the PV system. Poly(ethylene-terephthalate) (PET) is a critical component of PV module backsheets due to its dielectric properties and low cost. However, PET is susceptible to environmental stressors and degrades over time. Changes in the physical properties of nine PET grades were modeled after outdoor and accelerated weathering exposures to characterize the degradation process of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Another possible explanation can be found in the removal of the titanium isopropoxide catalyst by precipitation. Slow hydrolysis of this catalyst could lead to the formation of photochemically active titanium dioxide (TiO 2 ) species. , Note that for PET addition of TiO 2 has also been shown to have a beneficial effect on weathering stability. It is widely believed that polymer dissolution/precipitation results in removal of the polymerization catalyst, and as such it was expected that the precipitated PEF would be virtually free of residual titanium species. However, ICP-MS analyses showed that there is no significant difference in titanium concentration between the reactor grade and precipitated PEF and PET (Table S3), and thus an effect of residual titanium is unlikely.…”
mentioning
confidence: 99%
“…Another possible explanation can be found in the removal of the titanium isopropoxide catalyst by precipitation. Slow hydrolysis of this catalyst could lead to the formation of photochemically active titanium dioxide (TiO 2 ) species. , Note that for PET addition of TiO 2 has also been shown to have a beneficial effect on weathering stability. It is widely believed that polymer dissolution/precipitation results in removal of the polymerization catalyst, and as such it was expected that the precipitated PEF would be virtually free of residual titanium species. However, ICP-MS analyses showed that there is no significant difference in titanium concentration between the reactor grade and precipitated PEF and PET (Table S3), and thus an effect of residual titanium is unlikely.…”
mentioning
confidence: 99%
“…MMR modeling was chosen because it facilitates more than one outcome variable to be regressed onto the same set of predictors (Breiman & Friedman, 1997). MMR balances goodness of fit with interpretability because it provides coefficients that reflect the contribution of each term in the model (Gordon et al, 2018). Each MMR model assessed how a domain of grandmother allocare was correlated with Aim 1 outcomes (the 4 domains of mental health) and the Aim 2 outcome, cortisol.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 PET studied under both outdoor and accelerated lab-based exposure conditions show not just different stages of degradation, but also the synergistic effects of combined stressors since moisture as dew is an important stressor along with temperature and irradiance. 23 In PET degradation, the presence of water leads to synergistic photo-hydrolytic degradation in outdoor exposures, beyond photolytic degradation; simple exposure to humidity alone does not induce this photo-hydrolytic degradation. 21 This is an example where combined effects in a material or complex system are not simply additive, and cannot be studied "one at a time, in isolation" as a hallmark of the scientific method (controlling all other variables when studying the one of interest).…”
Section: Data-driven Modelingmentioning
confidence: 99%